A Factor Analysis Approach Towards a Study of the Factors Affecting Students’ Choice of Higher Education Institution: A Case Study of a Private Institution (Twintech International University College of Technology) - Ishak, Khamsiah (Journal of Social Economics Research, 2016)
This study was conducted to discover the input that will help in the strategic management of the educational institution. The input is focused on information of the factors affecting students’ choice of a higher educational institution. For private educational institutions, the input also aids them in strategic marketing to gain competitive advantage. Specifically the study was done to discover the most important underlying factor that affects students’ choice of an educational institution and also to show what aspects of the institutional factor are considered by students when they make their choices of educational institutions. This research followed a quantitative research design, where a survey, using a questionnaire, was used to gather the data on the factors that affect students’ choice criteria. By employing the pertinent research methodology, which is the Factor Analysis, more specifically the principal component analysis (P.C.A.) the researcher was able to reduce all the 51 items of students’ responses to six (6) significant factors. The overall findings revealed that students chose more institutional factors than other factors. Based on this finding, a one factor solution was discovered to the study of students’ choice, which is the factor of the "institution" with the highest factor loadings. No other studies had covered comprehensively all the items from the literature review (social, economic, physical, institutional and environmental, academic, marketing and administrative items) regarding students’ choice of tertiary education.